Formation of spinel CoFe2O4 nanoporous oxide layers by electrochemical anodization. (May 2021) - Ennassiri, Naima; Roth, Artjom; Ez-Zahraouy, Hamid; Es-Souni, Mohammed
Abstract: In the present letter, we report a simple method for fabricating self-ordered CoFe2 O4 nanoporous oxide layers by electrochemical anodization. For that, optimal electrolyte and anodization conditions were applied for anodizing the parent alloy FeCoV sheet, leading to an ordered nanoporous structure of CoFe2 O4 . The as-synthesized sample are characterized by Scanning Electron Microscopy (SEM), X-ray spectroscopy (EDS) and X-ray Diffraction (XRD). Our SEM findings showed nanopores size constant in the range of 15 nm independent of anodization potential. Also, our XRD measurements, along with the energy dispersive measurements confirm the transformation of the as-anodized nanoporous oxide layers into nanoporous oxide layers CoFe2 O4 phase. Highlights: CoFe2 O4 nanoporous oxide layer were successfully synthesized by electrochemical anodization. Obtained nanopores size remained constant in the range of 15 nm independent on anodization potential. The measurements confirm the transformation of the as-anodized nanoporous layer into CoFe2 O4 nanoporous oxide layer.